Pelaksanaan Sistem Pengawasan Hakim Konstitusi di Indonesia - Mustopa, Al Amin Syayidin Ali (UI Scholars Hub, 2022)
The supervision system for constitutional judges in Indonesia based on the 1945 Constitution and Law 24/2003 explicitly involves two forms of supervision, namely internal supervision by the Honorary Council and external supervision by the Judicial Commission. The supervisory system finally changed after the Constitutional Court Decision Number 005 / PUU-IV / 2006. After this decision, the supervision system for constitutional judges in Indonesia underwent a substantial change in the form of supervision that eliminated external supervision. The existing internal supervision system often changes in accordance with the current statutory regime and implementing regulations. Changes related to the existing internal supervision system are a reaction in order to optimize the enforcement of the supervisory system related to suspected ethical violations committed by constitutional judges. Thus, the form and mechanism of enforcement of the constitutional judge supervision system also has an equally important role in relation to the current constitutional judge supervision system. Therefore, this study aims to explain the supervision system of constitutional judges in accordance with the prevailing laws and regulations in Indonesia and provide an analysis of the implementation of the supervision system applied to constitutional judges in Indonesia during the establishment of the Constitutional Court. This research is a normative juridical research using qualitative methods through statutory studies, case studies, and comparative studies. Based on the analysis conducted, it is concluded that the supervisory system for constitutional judges applied in Indonesia is an internal supervision system enforced by the Ethics Council and the Honorary Council as regulated in the laws and regulations of the constitutional court. Then, regarding the implementation of the internal control system, the enforcement of ethical violations committed by constitutional judges can be divided into three periods with the supervisory agency and the enforcement mechanism in accordance with the rules of the constitutional court in effect at that time. Nonetheless, in relation to the supervision system for constitutional judges and its enforcement, it can still be optimized considering the frequent changes in the supervision system so that supervision becomes less effective and the supervisory institution is not strong in terms of both the institution and authority.